Use of Economic and Mathematical Modeling Tools in Planning Investments in Fixed Assets - Kulikova, Lidiya; Aminova, Diana; Lyzhova, Anna (International Journal of Criminology and Sociology, 2022)
In order to maximize the effectiveness of fixed assets use it is necessary to assess the impact of organizational factors on capital productivity of fixed assets, and also to assess the feasibility of capital investment in fixed assets. The purposes of the study are to design an economic-mathematical model that makes it possible to predict a value of capital productivity knowing the values of different factors, as well as to calculate the effectiveness of capital investment in fixed assets on the example of the regional branch of Tatarstan Energy Company. During the correlation and regression analysis of the Tatarstan energy company branch, the authors found that the cost of the active part of fixed assets has the greatest impact on the capital productivity of fixed assets, so the company is recommended to increase the active part of fixed assets. The proposed approach to scenario forecasting of capital investments in fixed assets allows to assess the prospects for changes in the company’s financial performance as a result indicator of the company’s performance.